Diagnosis of cattle disease as an effort to prevent the spread of FMD using the dempster shafer method in Langkat district - Savira, Padilla; Novriyenni, Novriyenni; Alfhi Syahri, Milli (Yayasan Bina Internusa Mabarindo, 2023)
Diseases in livestock, such as cattle, can have significant negative impacts on the livestock industry and human health. In this regard, the cow disease of greatest concern is Foot and Mouth Disease (FMD), which is a communicable disease that can spread quickly among the cattle population and have serious implications for animal welfare and agricultural sustainability. This study aims to develop a method for diagnosing cattle diseases, especially FMD, as a measure to prevent the spread of epidemics in Langkat District. The method used is the Dempster Shafer method, which is an artificial intelligence method that utilizes probability theory and belief theory to overcome uncertainty in the decision-making process.